Upaya yang dilakukan Guru untuk Meningkatkan Karakter Disiplin Siswa di SMK 2 Yayasan Perguruan Bandung - Sani Susanti; Fernanda Selina Hasugian; Imei Wulandari; Rama Yani Pakpahan; Yeni Magdalena Siahaan (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to identify the main challenges faced by teachers in the management of students' disciplinary character at SMK 2 Yayasan Perguruan Bandung as well as the efforts made by teachers to shape students' disciplinary character.Qualitative research methods were used with a focus on interviews as a data collection technique.The results of the interviews show that students' discipline and character problems are complex, influenced by internal and external factors such as family and social environments. Teachers use a behavioral counseling approach to help students change behavior and improve character. Thus, this study provides new insights for teachers and related parties in improving discipline management in schools. Improving students' disciplinary character does not only involve teachers, but also requires support from parents and students' social environment. Through this collaborative approach, it is hoped that a conducive learning environment can be created for the formation of quality student character.